Improving surgical quality of care: learning from 8,331 surgical medical malpractice cases - Qin Chen; Qin Chen; Xiaoyu Liu; Xiaoyan Liu; Pan Song; Xiaoyan Quan; Huarong Xiong; Dan Wang; Xiaoli Hu; Hua Zhang; Meihong Shi; Meihong Shi (Frontiers in Medicine)
ObjectiveThis study aimed to analyze the characteristics of surgical litigation cases and the risk factors that contribute to catastrophic compensation.MethodsWe downloaded and retrieved all cases related to surgical litigation cases from the China Jufaanli Database between 2008 and 2023. Multivariate logistic regression analysis was employed to identify independent risk factors that may contribute to catastrophic compensation.ResultsThis study included a total of 8,331 successfully resolved surgical litigation cases. Of these, 5,114 hospitals were defendants, with 25.34% of them involved in two or more lawsuits, thereby categorized as “repeat defendants.” The total compensation amount was $269,163,545, with the highest compensation reaching $540,008. Most surgical litigation cases were concentrated in the eastern regions of China, with tertiary hospitals being the most frequently involved. The most common type of injury outcome was patient death. Compensation amounts and high compensation rates for severe disability exceeded those for death (p < 0.05). Independent risk factors associated with catastrophic compensation in surgical medical liability disputes included: Eastern region (OR = 1.462, 95% CI 1.038–2.060), secondary liability (OR = 2.457, 95% CI 1.633–3.696), main liability (OR = 9.353, 95% CI 6.195–14.121), major or full liability (OR = 10.878, 95% CI 7.152–16.546), severe disability (OR = 24.605, 95% CI 3.395–178.337), neurosurgery (OR = 3.488, 95% CI 2.265–5.373), thoracic surgery (OR = 1.810, 95% CI 1.017–3.219), general surgery (OR = 2.465, 95% CI 1.593–3.816), hepatobiliary surgery (OR = 3.251, 95% CI 1.980–5.338), gastrointestinal surgery (OR = 2.260, 95% CI 1.391–3.671), cardiovascular surgery (OR = 2.544, 95% CI 1.367–4.733), vascular surgery (OR = 2.916, 95% CI 1.246–6.827), and spinal surgery (OR = 2.921, 95% CI 1.763–4.841).ConclusionThis study analyzes the characteristics of surgical medical malpractice disputes in China from multiple perspectives and identifies independent risk factors for catastrophic compensation in surgical malpractice litigation. Our research has the potential to aid medical institutions in preventing and reducing surgical malpractice disputes, while also contributing to the provision of improved surgical care and nursing services for patients.